Implementation of problem-based learning e-modules to enhance problem-solving skills on global warming - Rodhiyah, Salmaa Anisah; Suharno (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2024)
This study aims to describe the improvement of student’s problem-solving abilities through the implementation of a Problem-Based Learning (PBL) e-teaching module supported by Augmented Reality and an adventure game. The research involved 36 students from class X3 of SMA N 3 Sukoharjo and was conducted over two cycles spanning five weeks. Data were collected through observation, interviews, and tests, and analyzed using both qualitative and quantitative methods. The results showed that the implementation of the PBL-based e-teaching module significantly improved student’s problem-solving abilities. The improvement was indicated by an average n-gain score of 0.46 in cycle I, categorized as medium, and an average n-gain score of 0.90 in cycle II, categorized as high. In the pre-cycle, all problem-solving indicators were below 70%; in the first cycle, two indicators met the target (≥70%) and in the second cycle, all indicators exceeded the target. Future research is encouraged to explore the development of PBL-based e-modules across different grade levels and to examine their impact on other 21st-century skills.